IN VITRO AND IN SILICO ANTIOXYDAN - Touhami, Lanez; z, Benamara, Hacen, Adaika, Aicha (university of eloued جامعة الوادي, 2022)
The antioxidant activity of 3-nitrophenylferrocene (3NPF) and 3,3'-nitrophenylferrocene (3,3'NPF) and their reduced amines was measured using superoxide anion radical ( 2 O −. ). Binding parameters such as binding free energies and binding constants were also calculated. G sign and values suggest respectively the spontaneity and a strong interaction between the radical 2 O.− and all studied compounds. Molecular docking study showed that 3NPF is most inreactive compound against glutathione reductase enzyme having the the lowest docking scores of -16.96 kJ/mol. The two reduced forms were predected to be non-toxic and are not inhibitors of CYP450 2C19, 2D6 isoenzymes which suggests a decrease in their plasma concentrations and a rapid elimination route.
artical
Keywords: Cyclic voltammetry, superoxide anion radical, binding parameters, toxicity, docking, Glutathione.